A Mediação na Aprendizagem e Desenvolvimento de crianças com Transtorno do Espectro Autista: uma leitura na Perspectiva da Teoria Histórico-Cultural - Aires, Any Louize (2023)
In the first half of the 20th century, psychiatrists began to use the term "autism" after observing and describing behaviors exhibited by young children, such as difficulty in social interaction, restricted interests, echolalic speech, repetitive motor movements, among others. With the increase and advance of studies on the subject, the nomenclature to refer to all these behaviors has changed, becoming recognized today as Autism Spectrum Disorder (ASD), considered to be a neurodevelopmental disorder that can be manifested in the form of different behaviors. According to the American Psychiatric Association (APA) in the Diagnostic and Statistical Manual of Mental Disorders (DSM-V-TR), people with ASD have persistent difficulties in social interaction and communication, as well as restricted and repetitive patterns of behavior or interests (APA, 2023). This study is characterized as exploratory and bibliographical research, with a qualitative approach and aims to identify, analyze and understand - in the literature of the state of knowledge and in other research sources that deal with this theme - the concept of mediation from the perspective of the Historical-Cultural Theory (HCT), aiming at pedagogical work with children with ASD in their learning and development process and its contribution to teacher training. The specific objectives are to identify, analyze and understand: - the mediating role of parents of children with ASD; - the mediating role of teachers of children with ASD in ordinary schools and the mediating role of children without disabilities in ordinary schools in the learning/development process of children with ASD in the classroom. The bibliographic research refers to academic-scientific productions published between 2012 and 2022 in the following databases: Brazilian Digital Library of Theses and Dissertations (BDTD) and Coordination for the Improvement of Higher Education Personnel (CAPES). The results of the analysis of the data collected show the importance of mediation for the development and learning of children with ASD, since, as indicated in the literature, intentional and planned mediation - carried out by teachers, parents and students without disabilities and using mediating tools - enables children with ASD to explore different ways of playing and acting, contributing to the development of their Higher Psychological Functions (HPF), such as imagination, attention, memory, thinking, abstraction and language. It was also possible to see that, in addition to the mediating groups defined in the objectives of this study - teachers, parents and other students without disabilities in the ordinary classroom - there are other people in the school environment who act as mediators in the pedagogical work with children with ASD, which we call "Other mediating elements in the school environment", which include caregivers/school support professionals; pedagogical coordinators, librarians and tools such as the EAC board, technological devices, costumes, toys, etc. In moving towards understanding the concept of mediation in THC, we identified that intentional and planned mediation, as well as the use of instruments and signs as mediating xi elements, contributes significantly to the learning and development of these children, highlighting the importance of promoting training for teachers from this perspectiv